Ultrasonographic Studies of Follicular Activities in Clomiphene Citrate Treated Anoestrus Cows - Patil, Manjusha; lngawale, M.V.; Birade, H.S.; Anwar, A. Syed (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
An experiment on ultrasonographic studies of follicular activities in clomiphene citrate treated  anoestrus cows was conducted. Ultrasound scanning was performed to record the follicular activities  on alternate day throughout one estrous cycle for control group and from drug administration to  induction of estrus in treatment group. The postpartum induced estrus (treatment group) and regular  estrus (control group) differed highly significantly (p
Keywords: Follicle; Clomiphene; Postpartum regular estrus; Induced estrus; Ultrasonography